Does grandparenting pay off for the next generations? Intergenerational effects of grandparental care - Mara Barschkett; C. Katharina Spieß; Elena Ziege (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Grandparents act as the third largest caregiver after parental care and daycare in Germany, as in many Western societies. Adopting a double-generation perspective, we investigate the causal impact of this care mode on children's health, socio-emotional behavior, and school outcomes, as well as parental well-being. Based on representative German panel data sets, and exploiting arguably exogenous variations in geographical distance to grandparents, we analyze age-specific effects, taking into account counterfactual care modes. Our results suggest null or negative effects on children's outcomes: If children three years and older are in full-time daycare or school and, in addition, cared for by grandparents, they have more health and socio-emotional problems, in particular conduct problems. In contrast, our results point to positive effects on parental satisfaction with the childcare situation and leisure. The effects for mothers correspond to an increase of 11 percent in satisfaction with the childcare situation and 14 percent in satisfaction with leisure, compared to the mean, although the results differ by child age. While the increase in paternal satisfaction with the childcare situation is, at 21 percent, even higher, we do not find an effect on paternal satisfaction with leisure.
Keywords: D1; I21; I31; J13; J14; 330; grandparental childcare; socio-emotional outcomes; cognitive outcomes; parental well-being; instrumental variable